Pengaruh Motivasi Terhadap Produktivitas Kerja Pada Kantor BKKBN Sulawesi – Selatan - Ruliaty, Ruliaty; samsinar, samsinar (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
FILZAH NUR FAJRINA 2011 Effect of Motivation on Work Productivity In BKKBN Office Sulawesi - South. Supervised by Dr. Hj. Ruliaty, SE, MM and Ismail Badollahi, SE, M.Si. AK.CA. This study aims to determine the effect of Motivation on Work Productivity In BKKBN Office of South Sulawesi in order to increase productivity in the office. The method used in this research is the Research Library (library research) are implemented by way of holding direct study of some books as library materials that can support this research. Besides field research (field research), which held a direct visit to the object. Research has been established, the research conducted by the method of analysis used is Simple Regression Analysis which explains the motivation Effect on Productivity Work In South Sulawesi BKKBN office. Results of this research indicate that motivation influence on Productivity Work In South Sulawesi BKKBN office.